Analysis of epiphytic orchid diversity and its host tree at three gradient of altitudes in Mount Lawu, Java - NINA DWI YULIA; SUGENG BUDIHARTA; TITUT YULISTYARINI (Biodiversitas Journal of Biological Diversity, 2011)
Yulia ND, Budiharta S, Yulistyarini T (2011) Analysis of epiphytic orchid diversity and its host tree at three gradient of altitudes in Mount Lawu, Java. Biodiversitas 12: 225-228. The aim of this study was to observe epiphytic orchid diversity and their host trees at three different altitudes (1796, 1922 and 2041 m asl.) at southern part of Mount Lawu, District of Magetan, East Java. Line transect of 10 x 100 m was set up and then divided into ten plots (as replicates) of 10 x 10 m. At each plot, species name and number of individual of epiphytic orchids, and species name, number of individual and diameter at breast height (dbh) of host trees were recorded. The result showed that there were 19 species of epiphytic orchid recorded at the study sites. There were significantly different among gradient altitude in number of epiphytic orchid species (F = 3.7; df = (2, 27); P < 0.05). The highest number of species of epiphytic orchid was recorded at the altitude of 1922 m asl. (6.6 species/100 m2) while the highest number of individual was recorded at the altitude of 1796 m asl. (1337.7 individuals/100 m2). The study site at altitude of 1922 m asl. was recognized as the denser and richer in species of host trees (2.3 species/100 m2 and 3.5 individuals/100 m2 respectively). However, the highest basal area of host tree was recorded at the altitude of 2041 m asl. (4558 cm2/100 m2).